Controversies on religious law in Poland - the school catechesis case - Piotr Stańczyk (University of Lower Silesia, 2011)
Article deals with possibility of engaging problem of school catechesis with radical and critical paradigm of education. The main problem refers to freedom of religion as a one of the human rights and necessary conditions of freedom in education. A school catechesis is considered as a potential arena of ideological struggle between different world views, what in case of hierarchical educational system can provoke unacceptable, in democratic states, infringement of human rights. All kinds of religion pedagogy brig up danger of illegitimate proselytism.